Simulation based virtual learning environment in medical genetics counseling: an example of bridging the gap between theory and practice in medical education. Issue 1 (December 2016) - Makransky, Guido; Bonde, Mads; Wulff, Julie; Wandall, Jakob; Hood, Michelle; Creed, Peter; Bache, Iben; Silahtaroglu, Asli; Nørremølle, Anne
Abstract Background Simulation based learning environments are designed to improve the quality of medical education by allowing students to interact with patients, diagnostic laboratory procedures, and patient data in a virtual environment. However, few studies have evaluated whether simulation based learning environments increase students' knowledge, intrinsic motivation, and self-efficacy, and help them generalize from laboratory analyses to clinical practice and health decision-making. Methods An entire class of 300 University of Copenhagen first-year undergraduate students, most with a major in medicine, received a 2-h training session in a simulation based learning environment. The main outcomes were pre- to post- changes in knowledge, intrinsic motivation, and self-efficacy, together with post-intervention evaluation of the effect of the simulation on student understanding of everyday clinical practice were demonstrated. Results Knowledge (Cohen'sd  = 0.73), intrinsic motivation (d  = 0.24), and self-efficacy (d  = 0.46) significantly increased from the pre- to post-test. Low knowledge students showed the greatest increases in knowledge (d  = 3.35) and self-efficacy (d  = 0.61), but a non-significant increase in intrinsic motivation (d  = 0.22). The medium and high knowledge students showed significant increases in knowledge (d  = 1.45 and 0.36, respectively), motivation (d  = 0.22 and 0.31), and self-efficacy (d  = 0.36 and 0.52, respectively). Additionally, 90 % of students reported a greater understanding of medical genetics, 82 % thought that medical genetics was more interesting, 93 % indicated that they were more interested and motivated, and had gained confidence by having experienced working on a case story that resembled the real working situation of a doctor, and 78 % indicated that they would feel more confident counseling a patient after the simulation. Conclusions The simulation based learning environment increased students' learning, intrinsic motivation, and self-efficacy (although the strength of these effects differed depending on their pre-test knowledge), and increased the perceived relevance of medical educational activities. The results suggest that simulations can help future generations of doctors transfer new understanding of disease mechanisms gained in virtual laboratory settings into everyday clinical practice.